DISTRACTION OSTEOGENESIS OF A UNILATERAL HYPOPLASTIC MANDIBLE - Liaqat, Sahrish; Baig, Amir Mushtaq; Bukhari, Syed Gulzar Ali; Ahmed, Waseem (Journal of Ayub Medical College Abbottabad, 2011)
Summary: Distraction osteogenesis (DO) is a surgical process in which two bony segments are gradually separated so new soft tissue and bone will form between them by applying tension through a fixation device. There are three phases to this process: latency phase, distraction phase, and consolidation phase. The technique was originally applied to long bones but in recent years the method has been adapted for use in maxillofacial surgery. Distraction osteogenesis is a new variation of more traditional; orthognathic surgical procedures which can be applied for the correction of dento-facial deformities and syndromes of the jaws, treating upper airway obstruction in paediatric patients with mandibualr retrognathia, due to tongue collapse and physical obstruction in the hypopharangeal region. It is an effective and powerful reconstructive surgical technique, which can be performed safely without the need of bone graft or blood transfusion. We present treatment of a child with severe facial asymmetry after unilateral TMJ ankylosis corrected by distraction osteogenesis.